Characterization of carbon felt electrodes for vanadium redox flow batteries – A pore network modeling approach. (February 2019) - Banerjee, R.; Bevilacqua, N.; Eifert, L.; Zeis, R.
Highlights: Transport properties of commercially available carbon felt electrodes was calculated. Impact of pore structure and pore size distribution on permeability was shown. Imbibition curves showing capillary pressure – saturation relationship was discussed. Abstract: Carbon felt electrodes are commonly used as porous electrodes in Vanadium redox flow batteries for large-scale energy storage. The transport properties of these electrodes are an important parameter as the transport resistance can form a significant parasitic power loss depending on the configuration of the flow battery. Therefore, to better predict the overall parasitic power losses and devise strategies for the improvement of overall battery efficiency, the transport properties need to be properly understood. In this work, four commercially available carbon felt electrodes have been investigated for their transport properties. It has been shown that the non-activated electrode is hydrophobic in nature, while after activation, the electrodes become hydrophilic. The single-phase diffusion and permeability were found to decrease linearly with an increase in electrode thickness. The imbibition characteristics were similar for the four electrodes, although the change in wettability had a strong impact on the pressure required for the electrolyte to invade into the electrode.